The Impact of McGuigan's Strategy on Fifth-Grade Mathematics Achievement in Primary School Students. (Journal of the College of Basic Education, 2025)
The research aims to identify the effect of teaching mathematics using the McGuigan strategy on achievement among fifth-grade primary school students. Al-Sahoul Mixed Primary School affiliated with the General Directorate of Education in Diyala/Al-Khalis District was chosen intentionally, and the research sample consisted of (53) male and female students from the fifth-grade primary school students in the second semester of the academic year (2024-2025) AD, By random selection of the people, group (A) was chosen to be the experimental group that studied according to the McGuigan strategy with (27) male and female students, and group (C) was chosen to be the control group that studied according to the traditional method with (26) male and female students, and the two groups were rewarded in the following variables (intelligence, chronological age, previous information in mathematics, previous achievement in mathematics and the educational level of the parents), The achievement test in mathematics was prepared, consisting of (20) items, (15) objective multiple-choice items and (5) objective true-false items. Its validity, difficulty coefficient and discrimination of its items were verified using the Kuder-Richardson equation (KR-20). The value of the reliability coefficient was (0.879). After the experiment was completed, the achievement test in mathematics was applied to the two research groups (experimental and control). The statistical program 24spss_ was used to process the data statistically, and the results showed that there was a statistically significant difference at the significance level (0.05) between the average scores of the students in the experimental group and the scores of the students in the control group in the achievement test in mathematics, in favor of the experimental group according to the teaching method.There was no significant difference between the mean scores of the two rsearch groups according to the gender variable and the interaction between teaching mathod and gender.In light research results, a number of conclu, recomtendations, and proposals were reached.